The Islamic ethics of mitochondria transplantation - Bouzenita, Anke Iman; Mirghani, Mohamed Elwathig Saeed (Kulliyyah of Engineering, International Islamic University Malaysia, 2016)
Biotechnology has opened a new chapter with the advent of mitochondria transplantation for cell-based therapy. Mitochondrial transplantation was successfully led to birth; however, cytoplasmic transplantation has caused apprehension, since the mixing of human ooplasm from two different maternal sources may generate mitochondrial DNA (mtDNA) heteroplasmy in the offspring. Islamic legal verdicts on human cloning and somatic cell transfer have been overweighingly explicit as to its prohibition, due to the change of creation, mixing of lineage and other evaluations.Is mitochondria transplantation equivalent to human cloning in that genetic information is proliferated, and does it therefore take the same legal rule? Are there possible benefits (masalih) for medical treatment that may render mitochondria transplantation permissible, or are possible harms (mafasid) overweighing? Or is it a completely different procedure, taking a different rule?The paper will investigate into these questions and discuss the dimensions of Islamic ethics on the issue.